EKSPLORASI JAMUR AGENS HAYATI DARI RHIZOSFIR DI LAHAN GAMBUT DENGAN POLA TANAM YANG BERBEDA: Exploration of Fungal Biological Agents from the Rhizosphere in Peatlands with different Planting Patterns - Supriati, Lilies; Melhanah, Melhanah; Oemar, Oesin; Milenia, Safhira (AgriPeat, 2023)
There are several ways of cultivating crops that are applied by the community, namely: monoculture, insertion and agroforestry. Differences in the application and management of cropping patterns and the types of plants planted will have a different effect on microbes in the rhizosphere, especially fungi as biological agents. The purpose of this study was to determine the types of fungal biological agents found in the rhizosphere of several plants with different cropping patterns on peatlands. The location of the samples was determined purposively with insert cropping patterns (mustard-sweet corn), mono-culture (sweet corn) and agroforestry (jelutung-soursop). Testing the inhibition of biological agent fungi against Sclerotium rolfsii used a completely randomized design consisting of 7 treatments with 3 replications. The exploration results obtained 7 isolates of biologically active fungi that could inhibit S. rolfsii. The highest inhibition was shown by isolates JSk1 (origin from the rhizosphere of soursop plants), isolates J (origin from the rhizosphere of sweet corn) and JS1 (origin of the rhizosphere of mustard greens). JSk1 and J isolates had an inhibition close to 60%. The results of the identification of JSk1 isolates were the fungus Gliocladium sp1, isolate J the fungus Trichoderma harzianum with competitive inhibitory mechanisms, mycoparasites, antibiosis causing host hyphae to experience malformation, lysis and destruction.